(Mis)communicating climate change? Why online adaptation databases may fail to catalyze adaptation action. (19th May 2016) - Mitchell, Carrie L.; Burch, Sarah L.; Driscoll, Patrick A.
Abstract : Over the last decade a plethora of action‐oriented research projects has been conducted in developing countries, exploring how to effectively adapt to the anticipated impacts of climate change. Many intergovernmental agencies and development organizations have chosen to disseminate their research results via online databases. It is unclear, however, whether these databases are useful in terms of actual adaptation planning and implementation. A systematic review of online databases has found at least 64 databases and tools online related to climate change adaptation. Despite the abundance of databases, this analysis reveals that the existing body of online databases generally lack the structure and mechanics to identify, extract, and synthesize both effective and ineffective climate change adaptation practices, projects, programs, and policies. Even relatively basic information, such as identification of projects' projected versus actual costs is absent, which are crucial decision‐making criteria particularly in developing country contexts where resource constraints are significant. In this paper we evaluate these online tools with a focus on identifying features that potentially could contribute to knowledge sharing and successful exchange of climate change adaptation projects and practices within a developing country context. We conclude the paper with recommendations for how to improve efforts to communicate climate change research, such as more nuanced needs assessments of potential users of databases. WIREs Clim Change 2016, 7:600–613. doi: 10.1002/wcc.401 This article is categorized under: Vulnerability and Adaptation to Climate Change > Institutions for Adaptation Climate and Development > Knowledge and Action in Development Social Status of Climate Change Knowledge > Knowledge and Practice